The Current State of Criminological Research in the United States: An Examination of Research Methodologies in Criminology and Criminal Justice Journals. Issue 3 (2nd July 2016) - Woodward, Vanessa H.; Webb, Megan E.; Griffin, O. Hayden; Copes, Heith
Abstract : A recurring concern within criminology and criminal justice (CCJ) is how to best investigate criminological theory and criminal justice policy. To assess the current state of research, we conducted a content analysis of articles that appeared in seven CCJ journals over a two-year period (2013–2014). We then examined types and frequencies of data sources, analytic techniques, methodological approaches, and subject matters. Findings demonstrate that articles are predominantly employing quantitative methodologies and data where there is no participant contact. From these findings, we discuss the current state of research and how this could be used to guide graduate education, by recommending a variety of subject matters that graduate schools should emphasize in training new academics.